Reading comprehension: statistical analysis of test results for primary and secondary schools - Geld, Renata (Array, 2007)
The aim of the paper is to present results of the reading comprehension test for primary school (1254 subjects) and secondary school (656 subjects), with special regard to level of difficulty and achievement. The test was too easy for primary school learners (p=.42 to p=.93), but was appropriate for secondary school learners (p=.15 to p=.70). The factors that significantly influence reading comprehension achievement in primary school learners were overall school grade, learning English outside school, learning another foreign language, Internet use, length of learning English, motivation, self-assessment and attending a city school. For secondary school learners, the factors that significantly influence reading comprehension achievement were sex, number of hours of English per week, overall school grade, learning another foreign language, length of learning English, motivation, self-assessment and attending a grammar school (as opposed to a vocational school). A precise attribution of causes for these results can only be made after further experimental research, but some speculations are offered. The interpretation of test difficulty results points to the importance of the knowledge of language and the knowledge of the world in reading comprehension test achievement.